miR-4461 Regulates the Proliferation and Metastasis of Ovarian Cancer Cells and Cisplatin Resistance - Dou, Lei; Zhang, Yi (Frontiers in Oncology, 2021)
microRNAs (miRNAs) are of great significance in cancer treatment, which may have a desirable result on the regulation of tumorigenesis, progression, recurrence, and chemo-resistance of ovarian cancer. However, the research on the further potential application of miR-4461 in ovarian cancer is little and limited. Therefore, the study in this paper focus on the investigation of the of miR-4461 in ovarian cancer progression and chemo-resistance. The phenomenon that the proliferation and metastasis of ovarian cancer cells can be promoted by miR4461 is revealed in functional assays. Through the bioinformatics and luciferase reporter analysis, the PTEN is validated to be the direct target of miR-4461 in ovarian. The association between the expression of miR-4461 and PTEN is negative in in human ovarian cancer tissues. The distinction of growth and metastasis capacity between miR-4461 knockdown ovarian cancer cells and control cells is partially abolished by si-PTEN. Moreover, it was found that cisplatin treatment has obvious effect on the miR-4461 knockdown ovarian cancer cells. In summary, the data given in this paper indicate that the miR-4461 can be regarded as a potential onco-miRNA in ovarian cancer by targeting PTEN.